ANALISIS SPASIAL KINERJA JALAN DAN SIMPANG DI KABUPATEN KUDUS - Fitriani, Nurul; Andika, Fajar An Nashr; Wahyuseptiono, Muhamad; Syaban, Alfath Satria Negara; Wibowo, Nanang Ary (Jurnal Transportasi, 2023)
One of the keys to smooth traffic flow in an area is characterized by optimal road and intersection performance. Planning or evaluating roads and intersections certainly requires existing data information, so storing data digitally will make subsequent handling activities easier. As technology is easy to use, it is very helpful in storing and presenting data. Geographic Information Systems present images, check, integrate, manipulate, analyze and display data that relates to the topographic conditions of the earth. The aim of this research is to conduct a spatial analysis of road and intersection performance in the CBD of Kudus Regency using ArcGIS. The data in this research includes primary data and secondary data. Primary data includes data on traffic volume, speed, capacity, V/C ratio, degree of saturation, segment length and service level. Meanwhile, secondary data is road network data. After data analysis, road and intersection performance data were synchronized with road network data using ArcGIS. The results of this research provide an information system related to road and intersection performance, making it easier to handle roads and intersections in the CBD Area of Kudus Regency. ABSTRAK Salah satu kunci lancarnya arus lalu lintas di sebuah wilayah ditandai dengan kinerja jalan dan simpang yang optimal. Perencanaan ataupun evaluasi jalan serta simpang tentu membutuhkan informasi data eksisting, sehingga penyimpanan data secara digital akan mempermudah kegiatan penanganan selanjutnya. Seiring mudahnya penggunaan teknologi, sangat membantu dalam penyimpanan dan penyajian data. Sistem Informasi Geografis menyajikan gambar, mengecek, mengintegrasikan, memanipulasi, menganalisan dan menampilkan data yang menghubungkan kepada kondisi topografi bumi. Tujuan dari penelitian ini adalah melakukan analisis spasial kinerja jalan dan simpang di CBD Kabupaten Kudus menggunakan ArcGIS. Data pada penelitian ini meliputi data primer dan data sekunder. Data Primer antara lain data volume lalu lintas, kecepatan, kapasitas, V/C rasio, derajat kejenuhan, panjang segmen dan tingkat pelayanan. Sedangkan data sekunder yaitu data jaringan jalan. Setelah dilakukan analisis data, kemudian data kinerja jalan dan simpang disinkrongkan dengan data jaringan jalan menggunakan ArcGIS. Hasil dari penelitian ini menyajikan sistem informasi terkait kinerja jalan dan simpang, sehingga mempermudah dalam penanganan jalan dan simpang di Kawasan CBD Kabupaten Kudus.